2022
DOI: 10.1371/journal.pone.0267415
|View full text |Cite
|
Sign up to set email alerts
|

Making maternity and neonatal care personalised in the COVID-19 pandemic: Results from the Babies Born Better survey in the UK and the Netherlands

Abstract: Background The COVID-19 pandemic had a severe impact on women’s birth experiences. To date, there are no studies that use both quantitative and qualitative data to compare women’s birth experiences before and during the pandemic, across more than one country. Aim To examine women’s birth experiences during the COVID-19 pandemic and to compare the experiences of women who gave birth in the United Kingdom (UK) or the Netherlands (NL) either before or during the pandemic. Method This study is based on analyse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A recent study conducted in the United Kingdom and the Netherlands found that many women who have birth during COVID‐19 experienced restrictions, but their experience was mitigated by staff actions. We reinforce calls for the prioritisation and equitable distribution of individualised care in maternity care policy, rather than reliance of the benevolence of care providers 55 …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A recent study conducted in the United Kingdom and the Netherlands found that many women who have birth during COVID‐19 experienced restrictions, but their experience was mitigated by staff actions. We reinforce calls for the prioritisation and equitable distribution of individualised care in maternity care policy, rather than reliance of the benevolence of care providers 55 …”
Section: Discussionmentioning
confidence: 62%
“…We reinforce calls for the prioritisation and equitable distribution of individualised care in maternity care policy, rather than reliance of the benevolence of care providers. 55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an initial reduction in adverse outcomes during the pandemic (20)(21)(22). The increased proactivity and togetherness that the initial wave of the Covid pandemic inspired has been reported previously (23,24). This occurred alongside removal of barriers in making quick and effective changes to care, enabling Trusts to make large-scale changes; some that have remained in place.…”
Section: Strengths and Limitationsmentioning
confidence: 93%